2020
DOI: 10.1108/ijphm-04-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Pro-environmental behavior in nutricosmetics product purchase context

Abstract: Purpose Though the concern over pro-environmental behavior is growing, there is a lack of a valid scale to measure pro-environmental behavior in nutricosmetics context. Nutricosmetics products are believed to boost health and fitness and thus gained worldwide popularity. Many consumers in recent days are purchasing nutricosmetics products because of its positive impact toward human health and less harm toward the environment. However, to date, there is no valid instrument to measure this construct. To fill thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…It is reported that the Asian market of cosmetics has become one of the fastest growing markets [5]. The market value of the Asia Pacific region has increased to more than US$70 billion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the Asian market of cosmetics has become one of the fastest growing markets [5]. The market value of the Asia Pacific region has increased to more than US$70 billion.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the report by the Ministry of Health Malaysia, a total of 142,777 illegal cosmetics worth RM 3.4 million were confiscated in 2018 [5]. This phenomenon called for the research attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These three scales have consisted of 10 items, 3 items and 7 items, respectively. The PEB scale was a multidimensional second-order construct, which was borrowed from Quoquab et al (2020). The dimensions are, namely, environmental aesthetics interaction (4 items), conservative behaviour (7 items) and health consciousness (3 items).…”
Section: Methodsmentioning
confidence: 99%
“…Reflections on morals and social partners who support them concern for the environment significantly and positively affect the commitment to environmental sustainability. Their pro-environmental peered advocacy and environmental commitment influence their proenvironmental behavior collectively ( Denzin, 2012 [67][68][69][70][71][72][73][74][75][76][77].…”
Section: Pro-environmental Behaviormentioning
confidence: 99%